2012
DOI: 10.3126/nje.v2i2.6573
|View full text |Cite
|
Sign up to set email alerts
|

Situation of Iron Deficiency and Its Management Prioritizing Dietary Intervention in Nepal

Abstract: Background Control of iron deficiency disorders is prioritized in the nutrition policies of Nepal. The situation is still threatening the public health in both rural and urban areas. Objective There are limited reviews on the iron deficiency situation in Nepal. This study was undertaken to find out the extent of iron deficiency anemia and intake of dietary iron among the general population in Nepal. Materials and methods Published research articles, books, bulletins, and online materials regarding iron def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Pregnant women in the intervention group reflected behavioral change by practicing minimum of 3 or more meal consumption [ 23 ]. Nutrition education and counseling has been found in other studies to improve maternal diet including dietary practices and consumption of macro and micronutrients [ 10 , 24 ]. Micronutrient deficiencies can lead to poor maternal health outcome and pregnancy associated complication [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women in the intervention group reflected behavioral change by practicing minimum of 3 or more meal consumption [ 23 ]. Nutrition education and counseling has been found in other studies to improve maternal diet including dietary practices and consumption of macro and micronutrients [ 10 , 24 ]. Micronutrient deficiencies can lead to poor maternal health outcome and pregnancy associated complication [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women in the intervention group reflected a change in behavior by practicing a minimum dietary intake of 3 or more (19). Nutrition education and counseling have been found in other studies to improve maternal diet including dietary practices and consumption of macro and micro nutrients (8) (20). Micronutrient deficiencies can lead to poor maternal health outcomes and pregnancy-related complications (21).…”
Section: Discussionmentioning
confidence: 96%
“…This outcome is consistent with a research from Dessie Town that found that pregnant women who received nutrition education and counseling using the HBM had significantly improved dietary habits [ 31 ]. Other studies have shown that nutrition instruction and guidance can enhance maternal diet, including dietary habits and nutrient intake [ 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%